Prediction of bio-economically sustainable yield and optimum fishing effort for the Nile tilapia (Oreochromis niloticus L.) fishery of Lake Hawassa, Ethiopia - Alayou, Surafel; Tekle-Giorgis, Yosef (Ethiopian Journal of Science and Technology, 2025)
The Nile tilapia (Oreochromis niloticus, L. 1758) stock of Lake Hawassa, Ethiopia, was assessed to estimate bio-economically sustainable yield (MSY and MEY) and optimum fishing effort (fopt) using length-based analytical models (Jone’s Cohort Analysis and Thompson and Bell). Pertinent data (length, weight, catch, effort, etc.) were collected on a daily basis between May 2012 and June 2013 from the two landing sites, where fishermen at the northern and the southern part of the lake land their catch for retail. The assessment revealed an estimated current yield of 240.23 t/year and 216.33 t/year for the southern and northern part of the fishery of the lake, respectively. The predicted biologically maximum sustainable yield (MSY) was 240.2 t/year and 218.7 t/year for the southern and northern fishery, respectively, which were obtained at an F-factor of 1 and 1.5, respectively. On the other hand, the maximum economic return was generated from the southern and northern fishery at an F- factor of 0.8 and 1.4, respectively. Therefore, the level of effort at the time of sampling (F-current) should be reduced by 20 % for the southern fishery while the current effort of the northern fishery can be expanded by 40% in order to obtain the maximum economically sustainable yield. Accordingly, the optimum level of fishing effort (fopt) to be exerted at the lake level was estimated at about 650 nets per day in order to exploit O. niloticus stock of Lake Hawassa sustainably.